OTOMATISASI PENYIRAM TANAMAN BUAH NAGA BERBASIS IoT MENGGUNAKAN ENERGY PANEL SURYA (STUDI KASUS : SUGA FLORA) - Dion Pernandi; Bambang Santoso (CV. Multi Kreasi Media, 2023)
An Abstract Watering here still uses plastic gembor to water the plants one by one directly so that in this way the watering is late and irregular, also the water needed for the plant is sometimes too much or even a shortage so that the plant becomes dry even until the plant dies and in this way too a lot of energy draining gardeners. This problem can be overcome by a microcontroller based automatic watering system where watering takes place only when the plant requires intense water. An indicator to find out whether the water needed by plants is in accordance with their needs is by measuring the level of soil moisture. The method that will be used in this research is descriptive method or development research. Analysis is to analyze the software and hardware requirements needed in the process of making the system. The design includes the design of software (software) and hardware (hardware). Implementation is to implement the tool by making and assembling this problem can be overcome with a microcontroller based automatic watering system. With this tool can save time and energy in watering plants. This tool is able to measure the portion of water needed for watering plants.